Future Climate Under CMIP6 Solar Activity Scenarios - Jan Sedlacek; Timofei Sukhodolov; Tania Egorova; Arseniy Karagodin‐Doyennel; Eugene Rozanov (Earth and Space Science, 2023)
Abstract Predictions of solar activity in the future are difficult to make due to the chaotic state of solar dynamo and the high nonlinearity of physical processes on the Sun. Therefore, the Climate Intercomparison Project Phase 6 (CMIP6) used a statistical approach and recommended two different solar forcing scenarios for the simulations. The reference scenario was developed as the standard forcing, whereas the alternative forcing has lower solar activity (EXT CMIP6). In this study, we use both forcings in a set of experiments to explore the importance of the alternative CMIP6 solar forcing for future climate and ozone layer variability. In general, the difference in solar forcing scenarios is small, and thus most changes at the surface and at high altitudes are not significant. In addition, only the active phases of the Sun, which have the largest difference in amplitude of the forcing, are investigated. In this case, some statistically significant patterns emerge, mostly in the stratosphere, but still, the magnitude of the changes is not very large and a noticeable surface climate response to these changes is not expected and also not found. Our results indicate that low amplitude solar forcings such as the EXT CMIP6 or similar are not worthwhile considering during the next CMIP type of activities. The proposed solar irradiance decline does not represent any danger to the ozone layer.